Confessional and Migration Factors of Economic Development of the East Siberian Region - ARZUMANOV, Igor A.; KAMEDINA, Lyudmila V.; LICHICHAN, Oleg P. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research examines the issues related to the influence of confessional and migration factors on the processes of the integrated territorial development in the Russian Federation. The analysis of the documents of strategic planning of socio-economic and demographic territorial development employed the methods of cultural and religious studies as well as socio-cultural, comparative legal and formal legal methods in the framework of the dialectic approach. The research reveals a correlation between the destruction of socio-economic development processes and the demographic stagnation factor. An analysis of potential threats to sociopolitical stability as a result of the intensification of migration processes and the activities of religious institutions in the East Siberian region is given. It is concluded that the confessional factor potentially plays a destabilizing role in the implementation of federal targeted programs aimed at the integration of Russian society.